Superoxide Radical Generation Mediated Plasmodium berghei Infection in Swiss Mice - Satyajit Tripathy, Subhankari Prasad Chakraborty and Somenath Roy (Al Ameen Medical College, 2012)
Aim: This study was aimed to evaluate the duration dependent study to develop Plasmodium berghei infection in in vivo system. Methods: 200µl of infected blood containing 1X105 parasites was challenged in Swiss mice intraperitoneally for 5, 10 and 15 days. After sacrifice, parasitemia, O2.- generation, NADPH oxidase activity, NO generation of lymphocyte; MDA level, TrxR activity and haemolytic activity of infected RBC; activities of LDH, CRP level, SGOT and SGPT, NO release of serum; the MPO activity of serum, liver, spleen and kidney were studied. Results: O2.- generation, NADPH oxidase activity, NO generation of lymphocyte; LDH activity, CRP, SGOT, SGPT level and NO release of serum and TrxR, haemolytic activity were significantly increased than control; and also MDA level of infected RBC significantly increased as compared to control. These effects were the maximum after 10 days of challenge. Conclusion: The findings suggest that, P. berghei NK65 infection maximally develop after 10 days infection in Swiss mice.